The Effect of Financial Ratios on Dividend Policy with Sales Growth as a Moderating Variable in Technology Sector Companies Listed on the Indonesia Stock Exchange (2019–2023) - Ridhani Fahlika Siregar; Abdillah Arif Nasution; Fadli Fadli (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines the effect of financial ratios on dividend policy with sales growth as a moderating variable in technology sector companies listed on the Indonesia Stock Exchange during the period 2019–2023. Dividend policy is an important corporate decision because it reflects management considerations in balancing company growth and shareholder returns. The independent variables used in this research are profitability, liquidity, and leverage, while dividend policy is the dependent variable and sales growth acts as a moderating variable. Profitability is measured using Return on Assets (ROA), liquidity is proxied by the Current Ratio (CR), leverage is measured using the Debt to Equity Ratio (DER), and dividend policy is measured by the Dividend Payout Ratio (DPR). This study employs a quantitative approach using secondary data obtained from the annual financial statements of technology sector companies listed on the Indonesia Stock Exchange. The data are analyzed using multiple linear regression and moderated regression analysis.The results show that profitability does not have a significant effect on dividend policy, indicating that net profit generated during the year is not the main consideration in dividend distribution decisions within technology companies. Liquidity has a significant effect on dividend policy, suggesting that companies with stronger short-term financial conditions tend to have a greater ability to distribute dividends. Leverage also significantly affects dividend policy, implying that the level of corporate debt influences management decisions regarding dividend payments. Furthermore, sales growth does not moderate the relationship between profitability and dividend policy. However, sales growth is proven to moderate the effect of liquidity and leverage on dividend policy. These findings provide insights for management and investors in understanding dividend policy determinants in technology sector companies in Indonesia.